Electrocardiographic characteristics in young male patients with left primary spontaneous pneumothorax estimated by the collins equation - Pang-Yen Liu; Yen-Po Lin; Yi-Hwei Li; Zhi-Wei Su; Chih-Lu Han; Shih-Chung Huang; Chin-Sheng Lin; Fan-Chun Meng; Hsien-Tsai Wu; Gen-Min Lin (Indian Heart Journal, 2017)
Objective: To investigate the 12-lead surface electrocardiographic (ECG) findings in young male patients with left primary spontaneous pneumothorax (PSP) estimated by the Collins equation. Methods: From 2003 through 2008, 60 young male patients who had left PSP and 61 age-matched unaffected males were included for 12-lead ECG analyses. The PSP size was estimated by the Collins equation. Those with left PSP were divided into two groups: 1) large PSP ≥30% (n = 37), and 2) small PSP <30% (n = 23). The ECG in the unaffected was used as the normal control. Baseline demographic, anthropometric, and electrocardiographic findings including heart rate, P-QRS-T axes, wave intervals, and RS voltages were compared among three groups. Results: As compared to the unaffected, patients with left PSP had faster heart rate, longer QTc interval, greater QRS and T axes. With regard to RS amplitudes, greater R in lead aVR and V1, and deeper S in lead II indicating predominant rightward forces, and smaller R in lead I and V3-V6 indicating inferior leftward forces were present in patients with left PSP. Of these ECG findings, heart rate, S voltage in lead II and R voltage in V1 in the large PSP but not in the small PSP had greater values than that in the unaffected group. Conclusion: Among young male patients with left PSP estimated by the Collins method, the ECG showed faster heart beat and predominant rightward forces especially for those with large PSP.